1950
DOI: 10.1001/jama.1950.02910350007004
|View full text |Cite
|
Sign up to set email alerts
|

Ventilation in the Flow of Measles and Chickenpox Through a Community

Abstract: It may be recalled that this type of meningitis may be the result of contamination at the time of lumbar puncture, spinal anesthesia, trauma or operative pro¬ cedures involving the brain and spinal cord. In other instances it originates from foci of infection such as otitis media. In still other cases it represents one of the complications of bacteremia or sepsis. In the past, when recovery has taken place, usually after a fairly long period of weeks and months, it was attributed to drainage of the cerebrospin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

1976
1976
2016
2016

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(12 citation statements)
references
References 2 publications
0
12
0
Order By: Relevance
“…52 Seven studies supported UV lights as a means to reduce ARD rates, 41,44,46,48 -50,52 although the measured effects in two studies were small. 44,50 It was concluded from the four military studies 41,46,48,49 that larger effects were observed only with high UV irradiation, and the effect was considered to be too low to recommend its use. 48…”
Section: Resultsmentioning
confidence: 99%
“…52 Seven studies supported UV lights as a means to reduce ARD rates, 41,44,46,48 -50,52 although the measured effects in two studies were small. 44,50 It was concluded from the four military studies 41,46,48,49 that larger effects were observed only with high UV irradiation, and the effect was considered to be too low to recommend its use. 48…”
Section: Resultsmentioning
confidence: 99%
“…In constructing Tables 1-3, data were collected from the following sources: Influenza A virus subtype H5N1 commonly known as "Bird Flu" [32][33][34][35]; Chicken Pox (varicella-zoster virus infection) [36][37][38][39]; Chikungunya [40][41][42]; Dengue Fever [43,44]; Ebola [45][46][47]; Hepatitis B [48][49][50]; Human Immunodeficiency Virus (HIV) and HIV-untreated [51][52][53][54]; Marburg haemorrhagic fever [47,55]; Measles [56][57][58][59][60]; Middle East Respiratory…”
Section: Multidimensional Scaling Analysismentioning
confidence: 99%
“…In one study, guinea pigs that were exposed to air exhausted from rooms containing patients with infectious TB, and subsequently treated with germicidal UV radiation, were completely protected from infection with M. tuberculosis ,47,48 Other studies cite the effectiveness of germicidal UV radiation in hospitals, 49 military housing, 50 and classrooms. 51,52,53 One recent study noted that use of germicidal UV lamps reduced culturable airborne bacteria by 14-19% (M. tuberculosis was not used for the study); however, the lamps did not reduce the concentration of gram-positive, rod-shaped bacteria. 54 The effectiveness of germicidal UV radiation in killing airborne tubercle bacilli depends on the intensity of the UV radiation, the duration of contact the organism has with the UV radiation, and the relative humidity.…”
Section: A Backgroundmentioning
confidence: 99%